Performance analysis of generalized orthogonal code index modulation system - Lina BIAN; Huizhen FENG; Xiaoping JIN; Weizhong LOU; Chongxiao QU (Dianxin kexue)
In order to improve the transmission efficiency of the code index modulation (CIM) system, a generalized orthogonal code index modulation (GQCIM) system with lower complexity was proposed, which was a single input single output (SISO) system.CIM system used spreading codes and constellation symbols to transmit information, but only activated two spreading code indexes and one modulation symbol.GQCIM system overcame the limitation of only activating one modulation symbol at a time in a novel way, at the same time, made full use of the orthogonality of modulation symbols, increased the spreading code index to transmit more additional information bits, and improved the transmission efficiency of the system.In addition, the theoretical performance of GQCIM system was analyzed and derived the upper bound of bit error rate performance.Then the performance of GQCIM was verified by Monte Carlo simulation, and the theoretical and simulation performance of GQCIM system was found to be consistent.And under the same transmission efficiency, the results show that the performance of GQCIM system is better than the same orthogonal modulation system, such as generalized code index modulation (GCIM) system, CIM system, code index modulation aided quadrature spatial modulation (CIM-QSM) system, code index modulation aided spatial modulation (CIM-SM) system, pulse index modulation (PIM) system.